The Role of Photography Technique on The Visual of Campus’ Promotional Media (Case Study: UPN Veteran East Java) - A. B. Wibisono; A. T. Artanto (Future Science)
UPN Veteran of East Java (UPNVJT) is one of the new state universities designated in 2015. As one of the new state college, it is expected for UPN Veteran East Java to have broader vision of its future that enables to rise its competitive value with the other state colleges in the eyes of society and the prospective students. One step of this vision’s development is acquired through a decent campus promotion, because Surabaya has a large number of campuses and it takes the right steps to determine the positioning in the competition with the other state college. Research with the title Role of Photography Technique on Visual Media Promotion on Campus